2013
DOI: 10.2105/ajph.2012.301111
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers to Discussing HIV Prevention With Adolescents: Perspectives of HIV-Infected Parents

Abstract: Objectives We examined HIV-infected parents’ conversations about HIV prevention with their uninfected children, including what facilitated or hindered communication. Methods Parents with HIV/AIDS (n|=|90) who had children aged 10 to 18 years were recruited for a mixed method study from 2009 to 2010. Interviews assessed facilitators and barriers to discussing HIV prevention. A questionnaire identified the frequency and content of conversations, parental confidence level, and perceived importance of discussing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Our intergenerational session emphasizes parents’ critical role in informing their adolescents about sex, including about their perspectives and values. Resonating with our formative research, which found that adolescents are receptive to communication with their parents, research also indicates that adolescents want to discuss sex with their parents but that parents need improved communication skills ( 77 , 78 ).…”
Section: Discussionmentioning
confidence: 67%
“…Our intergenerational session emphasizes parents’ critical role in informing their adolescents about sex, including about their perspectives and values. Resonating with our formative research, which found that adolescents are receptive to communication with their parents, research also indicates that adolescents want to discuss sex with their parents but that parents need improved communication skills ( 77 , 78 ).…”
Section: Discussionmentioning
confidence: 67%
“…Literature on HIV risk in adult children of HIV positive mothers is limited. Protective factors in reducing HIV risk in African American women have consistently reported the importance of parent-child communication and family connectedness (Cederbaum, 2012; Cederbaum et al, 2013; Collins, Baiardi, Tate, & Rouen, 2015; Edwards, Reis & Weber, 2013; Hutchinson & Montgomery, 2007; Kaplan, Hormes, Wallace, Rountree, & Theall, 2016; Murphy, Roberts, & Herbeck, 2012; O’Sullivan, Dolezal, Brackis-Cott, Traeger, & Mellins, 2005). Among African American women, the mother-daughter bond has been cited as the most important relationship and describe mothers as the key person in providing information to them about health, sexuality, and HIV prevention (Cederbaum, 2012; Collins et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature so far, the role of community members has been heavily focused on psychosocial support [2,27,32], whereas the role of moderators has been focused on dealing with misinformation and community management in general [8,25,39]. Such dichotomous roles between community members and moderators place moderators as those who should play the “policing” roles, where moderators have to prune discussions that potentially produce misinformation.…”
Section: Introductionmentioning
confidence: 99%